Branded entertainment: Gender differences in reactions to star ratings. Issue 2 (31st January 2019) - Kim, Kacy; Park, Chanmo; Yoon, Sukki; Choi, Yung Kyun; Oh, Sangdo; Lee, Jooyoung
Abstract: The consumer behavior literature shows that men are externally focused and women are internally focused consumers. The authors conduct three studies to test gender differences in the use of media‐posted public ratings for deciding whether to recommend branded entertainment films. The Study 1 results indicate that men are more (less) likely to recommend films that have high (low) star ratings, but women are equally likely to recommend films regardless of star ratings. In an interesting twist, Study 2 results show that if women are momentarily distracted by being made more aware of their surroundings, they process information similarly to men and are more persuaded by public ratings. In Study 3, the authors replicate and extend the findings by including a no‐star control group and examining additional variables—film and brand attitudes and recommendations—with a no star rating control group. The overall results show that men (women) are more (less) likely to look to public ratings for forming film and brand attitudes and recommendations.